Corporate Social Innovation and Intrapreneurship in South Africa Through the Lens of Institutional Theory - du Plessis, Jeanne (Graduate School of Business (GSB), 2023)
As an institution, business creates wealth, life-changing innovation, livelihoods, and is a vehicle for self-expression and identity. Especially at scale, it is also often an engine of environmental destruction, inequality and social harm. The response of Corporate Social Responsibility (CSR) is increasingly falling short of stakeholder expectations. The separation of social impact and core business that characterises CSR in South Africa will not realise the promise of sustainable development. This requires a transformation in the way business is done – a systemic change that must start somewhere. Corporate Social Innovation is inspired by the idea that the strengths and scale of business can be applied to addressing our most pressing social concerns. It applies a company's core capabilities to creating simultaneous social and commercial value. Corporate Social Intrapreneurship is Corporate Social Innovation that is driven by change agents inside a company. This dissertation is a qualitative, inductive study of four cases of Corporate Social Intrapreneurship in companies in South Africa. Data was collected through interviews and documents and was analysed through the lens of institutional theory. This theoretical perspective enables an examination of the intrapreneurship process as an engagement with the elements of social structure that are present in organisations and the broader social systems around them. It sheds light on the individual-level actions and interactions that signal the earliest moments of institutional change. The findings are a rich descriptive account of the organisational context and nature of each project, and the intrapreneurship process as experienced by the intrapreneurs. The findings describe how intrapreneurs engage in legitimation and institutional work aimed at maintaining, creating or disrupting institutions; how they wield symbolic, cultural, social and material capital; and what influences their reflexivity and agency. The dissertation concludes with suggestions for future research, and implications for academia and practice emerging from the insights of these case studies.